Palliative care knowledge and attitudes towards end-of-life care of nurses in tertiary hospitals - Lazarus, Eilean R.; Muliira, Joshua K.; Al-Zaabi, Omar; Al-Khabori, Murtadha K.; Al Adawi, Mudhar M.; Al Mamari, Qasim (Curationis (Pretoria), 2025)
Background Efforts to increase access to palliative care (PC) must consider healthcare providers’ level of knowledge and attitude because both affect the quality of services. Nurses play essential roles in the delivery of PC, including end-of-life care. Objectives The study aimed to describe nurses’ readiness to provide PC in Oman by measuring PC knowledge and attitudes towards end-of-life care. Method A cross-sectional design was used. The Palliative Care Knowledge Questionnaire and the Modified Frommelt Attitude towards the Care of the Dying Scale were used to collect data from nurses (n = 1469) practising in government tertiary hospitals across Oman. Results The nurses exhibited suboptimal PC knowledge and positive attitudes towards end-of-life care. Significant differences were noted in some domains of knowledge and attitudes of nurses with different levels of professional experience. Attitude towards end-of-life care was associated with experience, caring for a dying family member, education and training in PC, religiosity, spirituality and age, but none was a significant predictor. The predictors of PC knowledge were gender, caring for a dying family member and education and training in PC. Conclusion Nurses in tertiary care settings in Oman have positive attitudes towards end-of-life care, but they lack optimal PC knowledge. The gaps in knowledge could be attributed to professional education, training and experience. Contribution The identified gaps in nurses’ PC knowledge could influence the provision of PC. Interventions are needed to sustain optimal knowledge and competencies to deliver quality PC to patients and their families.